Pertumbuhan dan Hasil Beberapa Varietas Sorgum di Lahan Gambut - Fatmawati, Eka; Abdurrahman, Tatang; Arifin, Nur (Perkebunan dan Lahan Tropika, 2024)
Sorghum is a cereal crop with potential for food security. In West Kalimantan, sorghum production and development are still lacking, especially in peatlands. Peatlands have serious constraints such as low pH, toxic compounds for plants, nutrient deficiencies, high nutrient leaching and low base saturation, and inhibition of nutrient absorption. This the study's objective is to ascertain the diversity of growth and yield of several sorghum varieties in peatlands. The study was conducted on street Sepakat 2, Pontianak City, with a research period of approximately 4 months starting in September-December 2023. This study used a Completely Randomized Design (CRD) with 6 treatments of sorghum varieties and 4 replications. The varieties used were Bioguma 1, Bioguma 3, Super 1, Kawali, Soper 6, and Soper 9. The parameters examined in the research encompassed  plant height, stem girth, leaf count, dry weight of plants, root volume, panicle length, dry weight of 100 seeds, and dry weight of seeds per crop. The results of the study showed that there is diversity of growth and yield of several sorghum varieties in peatlands. The variety suitable for planting in peatlands is the Super 1 variety and Kawali.